EMOTIONAL STATES OF STUDENTS IN THE TRANSITION TO HIGHER EDUCATION: AN EXPLORATORY APPROACH - Campos, Sofia (2024)
Introduction. The flow of migrants between different countries is a reality in Portugal, Spain and Belgium. As a consequence, one of the main concerns is the care of migrants in health services. This healthcare is not systematised in the good practice manuals that are available. There is no training in this area, neither in educational curricula nor in the continuous training of health professionals. Objectives. To find out migrants' perceptions of the health care they receive in the three countries. Method(s). Cross-sectional descriptive study in which we adopted a qualitative approach based on Grounded Theory carried out through focus groups and semi-structured telephone interviews. For the analysis process, the main dimensions around which the discourse is articulated were identified, differentiating the most relevant aspects of each topic, grouping the data around the categories related to the objective of the study. The software Atlas-ti 8 and N-Vivo were used for the analysis. Results. The main difficulties faced by migrants in health care are: poor access to the health care system; barriers to healthcare, mainly communication barriers; frequent discriminatory behaviours; poor structural cultural competence, especially due to the lack of translation and intercultural mediation resources; poor health system flexibility and biomedical orientation; and insufficient professional cultural competence. Conclusions. Difficulties of access to the health system are evident: lack of language skills, ignorance of the care itinerary and the perception of discriminatory treatment by health professionals. In addition, the improvement of the competence and cultural sensitivity of health professionals and system improvement strategies, such as translation and intercultural mediation, are proposed.